Cu-Ni-Sn-xAl copper alloy material and preparation method thereof
Through the preparation method of Cu-Ni-Sn-xAl copper alloy material, combined with hot press sintering and aging treatment, the problem of insufficient corrosion resistance of copper alloy materials in marine salt spray corrosion environment is solved, and high hardness, high strength and Wear resistance, suitable for a variety of applications.
Patent Information
- Application Number
- CN202411354988.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-31
AI Technical Summary
Existing copper alloy materials are prone to corrosion, have short life and low reliability in marine salt spray corrosion environments, making it difficult to develop Cu-Ni-Sn-xAl copper alloys with high hardness, high strength, high wear resistance and high corrosion resistance. Material.
Using the preparation method of Cu-Ni-Sn-xAl copper alloy material, Cu, Ni, Sn and trace element Al powders are mechanically mixed, and hot-pressed sintering and aging treatment are carried out to form Cu-Ni- with excellent hardness and corrosion resistance. Sn-xAl copper alloy material.
It realizes the high hardness, high strength, wear resistance and corrosion resistance of Cu-Ni-Sn-xAl copper alloy material, and is suitable for high-precision elastic components, marine equipment and bearings, significantly improving the wear resistance of the material and Corrosion resistance.
Smart Images

Figure CN119220855A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of copper alloy materials, and in particular relates to a Cu-Ni-Sn-xAl copper alloy material and a preparation method thereof. Background Art
[0002] In seawater environments, condensers of marine vessels, load-bearing parts and fasteners of marine elevated structures, connectors of seawater desalination pipeline systems, etc. often face problems such as easy corrosion, short life, and low reliability. Developing Cu-Ni-Sn-xAl alloy materials with high hardness, high strength, high wear resistance, and high corrosion resistance is an effective way to solve these problems.
[0003] Cu-Ni-Sn alloy is considered an ideal alloy material due to its excellent electrical and thermal conductivity, high strength, corrosion resistance and wear resistance. It is also an ideal substitute for non-toxic and low-cost Cu-Be alloy. As a typical age-hardening alloy, Cu-Ni-Sn alloy improves hardness and strength through the amplitude modulation decomposition strengthening mechanism, and its structure and performance can be optimized by adding trace elements, heat treatment and plastic deformation. In addition, Cu-Ni-Sn alloy also has excellent wear resistance, low friction coefficient and corrosion resistance. It is widely used in aerospace, electronics industry and other fields, especially suitable for manufacturing bearings, bushings, propellers and impellers.
[0004] In recent years, spark plasma sintering (SPS) technology has shown broad application prospects in the field of powder metallurgy sintering. Due to its advantages such as fast sintering speed, high sample density, simple and efficient operation, energy saving and environmental protection, it has become a powerful tool for preparing metal materials, nanomaterials and gradient functional materials.
[0005] In the development of Cu-Ni-Sn copper alloy materials, microalloying is an effective method to improve the performance of copper alloys. By adding one or several different trace elements to Cu-Ni-Sn alloys, the overall performance of the alloy can be significantly improved. Especially in salt solutions, the affinity of Al element to oxygen is much higher than that of copper, and it can form a composite protective film of Cu2O and Al2O3, which significantly improves the corrosion resistance of the material. In addition, studies have shown that Al element, as a basic and effective grain refining element, can be added to copper and copper alloys in an appropriate amount, which can not only refine the grains, but also improve the mechanical properties and corrosion resistance.
[0006] At present, a common challenge of copper alloy materials is how to develop copper alloy materials with high hardness, high strength, high wear resistance and high corrosion resistance (especially resistance to marine salt spray corrosion). Therefore, the present invention provides a high hardness, high strength, wear resistance and corrosion resistance Cu-Ni-Sn-xAl copper alloy material and a preparation method thereof. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a Cu-Ni-Sn-xAl copper alloy material and a preparation method thereof in view of the deficiencies of the above-mentioned prior art. The Cu-Ni-Sn-xAl copper alloy material has high hardness, high strength, wear resistance and corrosion resistance, and is widely used in the fields of high-precision elastic components, ship equipment and bearings.
[0008] To solve the above technical problems, the technical solution adopted by the present invention is: a Cu-Ni-Sn-xAl copper alloy material is made of the following raw materials in mass fraction: Ni 12.5%, Sn 5%, Al 0.5%~1.0%, and the balance is Cu.
[0009] The present invention also provides a method for preparing the above-mentioned Cu-Ni-Sn-xAl copper alloy material, which comprises:
[0010] S1. Mechanically mixing Cu powder, Ni powder, Sn powder and Al powder to obtain a mixed material;
[0011] S2, placing the mixture obtained in S1 into a graphite mold lined with graphite paper, and then hot pressing and sintering, and naturally cooling to room temperature to obtain a sintered product;
[0012] S3. Perform aging treatment on the sintered product obtained in S2, and naturally cool it to room temperature to obtain a Cu-Ni-Sn-xAl copper alloy material.
[0013] Preferably, the mechanical mixing time in S1 is 4 h to 5 h.
[0014] Preferably, the hot pressing sintering method in S2 is: under a pressure of 20 MPa to 30 MPa, the temperature is raised from room temperature to 860° C. to 880° C., and constant temperature sintering is performed for 25 min to 35 min.
[0015] Preferably, the aging treatment method in S3 is: heating to 380°C to 420°C at a heating rate of 7°C / min, and keeping the temperature constant for 220min to 260min.
[0016] Preferably, the Cu-Ni-Sn-xAl copper alloy material in S3 has a Brinell hardness of 322 HB to 360 HB, a yield strength of 649 MPa to 790 MPa, and a corrosion current density of 2.088×10 -5 A / cm 3 ~2.342×10 -5 A / cm 3 The wear rate at room temperature is 0.568×10 -5 mm 3 / N·m~0.671×10 -5mm 3 / N·m, the wear rate at 500℃ is 48.1×10 -5 mm 3 / N·m~61.1×10 -5 mm 3 / N·m.
[0017] Compared with the prior art, the present invention has the following advantages:
[0018] 1. In the Cu-Ni-Sn-xAl copper alloy material prepared by the present invention, the three metal elements of Cu, Ni and Sn together constitute the Cu-Ni-Sn alloy matrix, and the alloy matrix ensures the hardness and strength of the alloy under the premise of saving materials. At the same time, trace element Al is introduced to enhance the aging hardening effect and mechanical properties of the Cu-Ni-Sn alloy. The addition of trace Al elements can significantly refine the grains of the alloy and effectively inhibit the formation of discontinuous precipitation phases, thereby improving the hardness, yield strength and wear resistance of the alloy matrix. The introduction of Al elements also significantly improves the uniformity of the microstructure and grain size of the Cu-Ni-Sn alloy, especially promotes the uniform distribution of Ni and Sn elements, reduces the driving force of selective phase corrosion, and makes the oxide layer formed by the preferentially dissolved γ phase more uniform, thereby enhancing the protective effect of the alloy. In addition, the Al2O3 protective layer formed by trace Al on the alloy surface can prevent the diffusion and migration of Cu+, inhibit the dissolution of Cu on the alloy surface, and significantly improve the corrosion resistance of the alloy. Therefore, the Cu-Ni-Sn-xAl copper alloy material of the present invention exhibits excellent high hardness, high strength, wear resistance and corrosion resistance, and is suitable for fields such as high-precision elastic components, ship equipment and bearings.
[0019] 2. In the present invention, by adding a trace amount of Al element, the effect of fine grain strengthening and inhibition of discontinuous precipitation is achieved, thereby effectively improving the hardness, strength, wear resistance and corrosion resistance of the alloy. In addition, during the sintering process, a thin layer of graphite paper is lined inside the graphite mold to ensure that the sintered sample can be demolded smoothly. Aging treatment further promotes the amplitude modulation decomposition strengthening and precipitation strengthening of the organizational structure, so that the hardness and strength of the material are further improved. The Cu-Ni-Sn-xAl copper alloy material prepared by the present invention is widely used in the fields of high-precision elastic components, ship devices and bearings.
[0020] The present invention is further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a SEM image of the cross-section of the Cu-Ni-Sn-xAl copper alloy material after corrosion prepared in Example 1 of the present invention.
[0022] Figure 2 This is a SEM image of the micromorphology of the Cu-Ni-Sn-xAl copper alloy material prepared in Example 1 of the present invention.
[0023] Figure 3 It is a bar chart of the hardness and yield strength of the Cu-Ni-Sn-xAl copper alloy of Examples 1-2 of the present invention and Comparative Example 1.
[0024] Figure 4 This is a bar chart of the average wear rate of the Cu-Ni-Sn-xAl copper alloy materials of Examples 1-2 of the present invention and Comparative Example 1 after friction tests at room temperature and 500°C. DETAILED DESCRIPTION
[0025] Example 1
[0026] The Cu-Ni-Sn-xAl copper alloy material of this embodiment is made of the following raw materials in mass fractions: Ni 12.5%, Sn 5%, Al 1.0%, and the balance is Cu.
[0027] This embodiment also provides a method for preparing the above-mentioned Cu-Ni-Sn-xAl copper alloy material, which is:
[0028] S1, mechanically mixing Cu powder, Ni powder, Sn powder and Al powder for 5 hours to obtain a mixed material;
[0029] S2, the mixed material obtained in S1 is loaded into a graphite mold lined with graphite paper, and then the mixture is subjected to rapid hot pressing sintering by a spark plasma sintering (SPS) device. Under a pressure of 30 MPa, the temperature is raised from room temperature to 860° C., and the mixture is sintered at a constant temperature for 25 min. After naturally cooling to room temperature, a sintered product is obtained;
[0030] S3. The sintered product obtained in S2 is subjected to aging treatment by heating to 420°C at a heating rate of 7°C / min, maintaining the temperature for 220 minutes, and naturally cooling to room temperature to obtain a Cu-Ni-Sn-xAl copper alloy material.
[0031] Figure 1 This is a SEM image of the cross section of the Cu-Ni-Sn-xAl copper alloy material prepared in this embodiment after corrosion. From this figure, it can be seen that the corrosion pits of the Cu-Ni-Sn-xAl copper alloy are shallow and there are products attached to the corrosion surface. The addition of Al allows a relatively uniform corrosion product film to be formed on the surface of the Cu-Ni-Sn copper alloy. At the same time, the presence of the corrosion product film can better hinder the erosion of corrosive ions, and the corrosion resistance is better.
[0032] In this embodiment, a uniform copper solid solution and CuNi2Sn phase are formed in the alloy, thereby significantly improving the hardness and strength of the alloy ( Figure 2). The addition of trace Al elements can effectively refine the grains of Cu-Ni-Sn alloy, thereby enhancing its hardness, strength and wear resistance. In addition, the addition of Al elements can also change the morphology of the lamellar γ phase structure, making the γ phase easier to precipitate in a granular morphology and distribute at the grain boundaries. These granular structures can hinder grain boundary migration, further refine the alloy grains, and improve their hardness, strength and wear resistance. At the same time, the addition of trace Al elements significantly inhibits the large-area precipitation of the γ phase, promotes the uniform distribution of Ni and Sn elements in the Cu-Ni-Sn alloy, and reduces the driving force of selective phase corrosion. During the corrosion process, the formation of Al2O3, CuO, Cu2O and NiO forms a composite protective film that is tightly and densely bonded to the matrix. This layered composite film greatly improves the corrosion resistance of the Cu-Ni-Sn alloy.
[0033] Example 2
[0034] The Cu-Ni-Sn-xAl copper alloy material of this embodiment is made of the following raw materials in mass fractions: Ni 12.5%, Sn 5%, Al 0.5%, and the balance is Cu.
[0035] This embodiment also provides a method for preparing the above-mentioned Cu-Ni-Sn-xAl copper alloy material, which is:
[0036] S1, mechanically mixing Cu powder, Ni powder, Sn powder and Al powder for 4 hours to obtain a mixed material;
[0037] S2, the mixed material obtained in S1 is loaded into a graphite mold lined with graphite paper, and then a spark plasma sintering (SPS) device is used for rapid hot pressing sintering, and the temperature is raised from room temperature to 880° C. under a pressure of 20 MPa, and the mixture is sintered at a constant temperature for 25 min, and then naturally cooled to room temperature to obtain a sintered product;
[0038] S3. The sintered product obtained in S2 is subjected to aging treatment by heating to 380°C at a heating rate of 7°C / min, maintaining the temperature for 260 minutes, and naturally cooling to room temperature to obtain a Cu-Ni-Sn-xAl copper alloy material.
[0039] Comparative Example 1
[0040] The Cu-Ni-Sn copper alloy material of this comparative example is made of the following raw materials in mass fractions: Ni 12.5%, Sn 5%, and the balance Cu.
[0041] This comparative example also provides a method for preparing the above-mentioned Cu-Ni-Sn copper alloy material, which is:
[0042] S1, mechanically mixing Cu powder, Ni powder and Sn powder for 5 hours to obtain a mixed material;
[0043] S2, the mixed material obtained in S1 is loaded into a graphite mold lined with graphite paper, and then a spark plasma sintering (SPS) device is used for rapid hot pressing sintering, and the temperature is raised from room temperature to 870°C under a pressure of 25 MPa, and the mixture is sintered at a constant temperature for 30 minutes, and then naturally cooled to room temperature to obtain a sintered product;
[0044] S3. Performing aging treatment on the sintered product obtained in S2, heating the temperature to 400°C at a heating rate of 7°C / min, keeping the temperature constant for 240 minutes, and naturally cooling to room temperature to obtain a Cu-Ni-Sn copper alloy material.
[0045] The physical properties, mechanical properties and corrosion resistance of the Cu-Ni-Sn-xAl copper alloy materials prepared in Examples 1-2 and Comparative Example 1 were tested, and the test results are shown in Table 1. The specific test method is: the density of the Cu-Ni-Sn-xAl copper alloy after SPS sintering is measured using the Archimedes method; according to GB / T 231.4-2009 / ISO The Brinell hardness of the copper alloy material was tested on a HBS-3000 touch screen Brinell hardness tester according to the method in GB / T7314-2005. The load applied during the test was 187.5 kgf, the holding time was 30 s, and the diameter of the indenter was 2.5 mm. According to the room temperature compression test method for metal materials in GB / T7314-2005, the yield strength of the copper alloy material was tested using a UTM5205 electronic universal testing machine at a compression rate of 0.1 mm / min. The corrosion resistance of the copper alloy material was tested by using a solution of 3.5 wt.% NaCl prepared with analytical pure NaCl to simulate a corrosion environment. The open circuit potential and polarization curve tests were completed using an electrochemical workstation (CHI660E). A three-electrode system was used, with the sample as the working electrode, the counter electrode as a platinum electrode, and the saturated calomel electrode as the reference electrode. The working area was about 1 cm 2 The scanning rate of the polarization curve is 1mV / s, and the scanning interval is -0.8V-1.2V; the friction and wear test of the copper alloy material at room temperature is carried out on a ball-disc high-temperature friction and wear tester. The disc sample is the sample to be tested, and the ball sample to be ground is a commercial Si3N4 ceramic ball with a diameter of 6mm. The conditions of the friction and wear test are as follows: the load is 5N, the rotation radius is 4mm, the motor frequency is 9.56Hz, and the sliding time is 30min.
[0046] Table 1 Properties of Cu-Ni-Sn-xAl alloy materials prepared in Examples 1-2 and Comparative Example 1
[0047] project Example 1 Example 2 Comparative Example 1 <![CDATA[Density (g / cm 3 )]]> 8.83 8.89 8.73 Brinell hardness (HB) 360 322 244 <![CDATA[Yield strength (MPa) σ 0.2 > 790 649 478 Corrosion potential (V) -0.340 -0.341 -0.342 <![CDATA[Corrosion current density (A / cm 3 )]]> <![CDATA[2.088×10 -5 ]]> <![CDATA[2.342×10 -5 ]]> <![CDATA[2.460×10 -5 ]]> Friction coefficient (room temperature) 0.55 0.59 0.62 <![CDATA[Wear rate (×10 -5 mm 3 / N·m)]]> 0.568 0.671 1.25 Friction coefficient (500℃) 0.46 0.44 0.48 <![CDATA[Wear rate (×10 -5 mm 3 / N·m)]]> 48.1 61.1 62.2
[0048] It can be seen from the test results of Table 1 that the Cu-Ni-Sn-xAl copper alloy material prepared in Example 1-2 exhibits high hardness and strength, which indicates that the material should have excellent wear resistance and resistance to plastic deformation in the application of parts. At the same time, during the friction and wear process, the alloy material exhibits good wear resistance regardless of room temperature or high temperature conditions. In addition, in a simulated salt solution corrosion environment, the alloy material also exhibits good corrosion resistance. Therefore, the Cu-Ni-Sn-xAl copper alloy material of the present invention is very suitable for use in fields such as high-precision elastic components, ship components, and bearings.
[0049] Figure 3 The figure is a bar graph of the hardness and yield strength of the Cu-Ni-Sn-xAl copper alloy material of Examples 1-2 and Comparative Example 1. It can be seen from the figure that the mechanical properties of the Cu-Ni-Sn-xAl copper alloy material are significantly improved compared with the pressureless sintered Cu-12.5Ni-5Sn copper alloy material. The hardness of the pressureless sintered Cu-12.5Ni-5Sn copper alloy material is 108HB and the yield strength is 298MPa.
[0050] Figure 4 The figure is a bar chart of the average wear rate of the Cu-Ni-Sn-xAl copper alloy materials of Examples 1-2 and Comparative Example 1 after friction tests at room temperature and 500°C. It can be seen from the figure that the average wear rate of the alloy in Example 1 is significantly reduced and the wear resistance is significantly improved. (In the figure caption, CNS is the alloy of Comparative Example 1, 1.0Al is the alloy of Example 1, and 0.5Al is the alloy of Example 2)
[0051] By comparing the performance of the alloy of the present invention with other high-strength and high-hardness alloys, it is found that the present invention controls and utilizes the interaction between elements well by adjusting the addition amount of trace element Al in the copper alloy, and controls the processing technology and heat treatment technology, so that the strengthening mechanisms such as aging hardening and fine grain strengthening of the alloy can fully play a role, so that the copper alloy of the present invention has more excellent mechanical properties than traditional tin bronze, wherein the hardness reaches about 360HB and the yield strength reaches about 790MPa. It is also found that the Al element has a great influence on the corrosion resistance of the alloy, and the addition of an appropriate amount of Al can significantly improve the strength and corrosion resistance of the alloy.
[0052] The tribological properties of the alloy of the present invention are compared with those of similar copper alloys. The wear rate of the pressureless sintered Cu-12.5Ni-5Sn alloy at room temperature is 2.9×10 -5 mm 3 / N·m, the wear rate at 500℃ is 7.1×10 -4 mm 3 / N·m; the wear rate of hot-pressed sintered Cu-12.5Ni-5Sn-0.4Y alloy at room temperature is 1.15×10 -5 mm 3 / N·m, the wear rate at 500℃ is 8.64×10 -4 mm 3 / N·m; while the wear rate of the alloy of the present invention is reduced to 5.68×10 -6 mm 3 / N·m, the wear rate at high temperature is reduced to 4.81×10 -4 mm 3 / N·m, the wear resistance is significantly improved.
[0053] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A Cu-Ni-Sn-xAl copper alloy material, characterized in that: The invention is made of the following raw materials in mass fractions: Ni 12.5%, Sn 5%, Al 0.5%-1.0%, and the balance Cu.
2. A method for preparing the Cu-Ni-Sn-xAl copper alloy material as claimed in claim 1, characterized in that: The method is: S1. Mechanically mixing Cu powder, Ni powder, Sn powder and Al powder to obtain a mixed material; S2, placing the mixed material obtained in S1 into a graphite mold lined with graphite paper, and then hot pressing and sintering, and naturally cooling to room temperature to obtain a sintered product; S3. Perform aging treatment on the sintered product obtained in S2, and naturally cool it to room temperature to obtain a Cu-Ni-Sn-xAl copper alloy material.
3. The method according to claim 2, characterized in that The mechanical mixing time in S1 is 4 to 5 hours.
4. The method according to claim 2, characterized in that: The sintering method of the hot pressing sintering in S2 is: under the condition of a pressure of 20MPa to 30MPa, the temperature is raised from room temperature to 860°C to 880°C, and the constant temperature sintering is performed for 25min to 35min.
5. The method according to claim 2, characterized in that: The aging treatment method described in S3 is: heating to 380°C to 420°C at a heating rate of 7°C / min, and keeping the temperature constant for 220min to 260min.
6. The method according to claim 2, characterized in that The Brinell hardness of the Cu-Ni-Sn-xAl copper alloy material in S3 is 322HB~360HB, the yield strength is 649MPa~790MPa, and the corrosion current density is 2.088×10 -5 A / cm 3 ~2.342×10 -5 A / cm 3 The wear rate at room temperature is 0.568×10 -5 mm 3 / N·m~0.671×10 -5 mm 3 / N·m, the wear rate at 500℃ is 48.1×10 -5 mm 3 / N·m~61.1×10 -5 mm 3 / N·m.